2021
DOI: 10.1186/s12885-021-08160-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the preoperative prognostic nutritional index as a predictor for postoperative complications after resection of locally recurrent rectal cancer

Abstract: Background Local recurrence is common after curative resections for rectal cancer. Surgical intervention is among the best treatment choices. However, achieving a negative resection margin often requires extensive pelvic organ resections; thus, the postoperative complication rate is quite high. Recent studies have reported that the inflammatory index could predict postoperative complications. This study aimed to validate the correlation between clinical factors, including inflammatory markers, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…However, extensive pelvic organ resection is usually needed to obtain a negative margin, which leads to a high incidence of postoperative complications, and serious complications will compromise the prognosis of patients. One study by Paku et al [27] has revealed that low preoperative nutritional prognosis index and excessive In our present study, after radical resection of RC, patients with presacral tumour recurrence showed a notably higher tumour metastasis rate and a notably higher longterm tumour recurrence rate than those without presacral tumour recurrence. According to the K-M curves, patients with presacral tumour recurrence had worse distant metastasis, total recurrence, and long-term recurrence than those without it.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, extensive pelvic organ resection is usually needed to obtain a negative margin, which leads to a high incidence of postoperative complications, and serious complications will compromise the prognosis of patients. One study by Paku et al [27] has revealed that low preoperative nutritional prognosis index and excessive In our present study, after radical resection of RC, patients with presacral tumour recurrence showed a notably higher tumour metastasis rate and a notably higher longterm tumour recurrence rate than those without presacral tumour recurrence. According to the K-M curves, patients with presacral tumour recurrence had worse distant metastasis, total recurrence, and long-term recurrence than those without it.…”
Section: Discussionsupporting
confidence: 52%
“…However, extensive pelvic organ resection is usually needed to obtain a negative margin, which leads to a high incidence of postoperative complications, and serious complications will compromise the prognosis of patients. One study by Paku et al [ 27 ] has revealed that low preoperative nutritional prognosis index and excessive intraoperative blood loss are risk factors for severe postoperative complications of locally recurrent RC, which can improve the prevention of severe postoperative complications of locally recurrent RC to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown the association between prognostic nutritional index (PNI) and prognosis of various malignancies in recent years [ 8 12 ]. PNI is derived from the following formula: serum albumin (g/L) + 5 × peripheral lymphocyte count (10 9 /L), which both evaluates the nutrition and immunologic status of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on PNI in rectal cancer, Wang et al ( 14 ) found that preoperative PNI was an independent predictive factor in predicting permanent stoma in patients who underwent AR and defunctioning stoma. Paku et al ( 15 ) found that low preoperative PNI was a risk factor posing influence on postoperative major complications of locally recurrent rectal cancer. Xia et al ( 16 ) found that it is rewarding to use PNI to predict postoperative complications in patients with T1–2 rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, current studies on PNI in rectal cancer are insufficient. PNI is associated with the permanent stoma rate after anterior resection and defunctioning stoma ( 14 ), postoperative complications of locally recurrent rectal cancer ( 15 ), and postoperative complications of early rectal cancer ( 16 ). However, regarding the connection between PNI and postoperative surgical complications after laparoscopic surgery for rectal cancer, seldom reports are published.…”
Section: Introductionmentioning
confidence: 99%